Natural Moxibustion Enhances Budesonide Inhalation Efficacy by Downregulating MMP-9 and TGF-β1 in Asthmatic Rats - Xiao-Ning Yan; Chang-Miao Niu; Yue Qu; Jin Guan; Yan-Hong Qin (World Journal of Traditional Chinese Medicine, 2025)
Objective: To explore the effects of natural moxibustion on inhibition of airway remodeling in bronchial asthmatic rats. Materials and Methods: Sprague Dawley rats were treated with ovalbumin to establish an asthma model. The ancient prescription of natural moxibustion, named Bai-Jie-Zi pulvis, was applied by pasting acupoints in combination with budesonide suspension inhalation to treat the asthmatic models for a consecutive period of 14 days. Histopathological changes were then observed and assessed. The cytokines involved in airway remodeling progression, namely matrix metalloproteinase 9 (MMP-9) and transforming growth factor beta-1 (TGF-β1) in lung tissue, were measured using immunohistochemistry and western blotting. The positive control group received treatment solely by inhalation of budesonide. Results: Combination therapy with budesonide suspension inhalation and natural moxibustion demonstrated significant improvements in inflammatory cell infiltration, bronchial mucus plug secretion, terminal bronchial obstruction, and edema in the lung tissue compared with the model (MOD) group (P < 0.01, P < 0.05, P < 0.01, respectively). In addition, an enhanced effect in relieving branchial mucous plug secretion was observed in the BUD + BJZ group (P < 0.01). Both MMP-9 and TGF-β1 expression were downregulated compared to the group treated solely with budesonide suspension inhalation (P < 0.05, P < 0.01, respectively). Conclusions: The combination therapy of natural moxibustion and budesonide inhalation demonstrated a synergistic effect in asthmatic rats, effectively inhibiting the airway remodeling process. This traditional external therapy exhibited efficacy in asthmatic rats and may potentially serve as a complementary approach in the treatment of asthma.